The attitudes of medical students toward the importance of understanding classical Greek and Latin in the development of an anatomical and medical vocabulary. Issue 6 (4th April 2016) - Stephens, Shiby; Moxham, Bernard John
Abstract : Students on entering medical school are faced with acquiring new, and voluminous, anatomical and medical terminologies. A reason why acquiring these terminologies may be problematic relates to the fact that many terms are derived from classical Greek and Latin; languages nowadays that are rarely taught at school. It might also be supposed that the often reported reduction in exposure to anatomy, and time spent in the dissection room, impairs the students' knowledge and understanding of anatomical relationships, and thus further complicates the acquisition of the terminologies. To date, there have been no studies that have quantified the attitudes of medical students toward the importance of understanding classical Greek and Latin during their medical training. In order to assess these attitudes, this study was undertaken for the newly‐recruited (First Year) medical students and for the Final Year medical students at Cardiff University. They were provided with a brief questionnaire that was devised in accordance with Thurstone and Chave (1951) principles and with ethical approval. One hundred and eighty First Year students and one hundred and nineteen Final Year students responded. Our initial hypothesis was that students throughout the medical curriculum have an unfavorable attitude toward the importance of classical Greek and Latin. This hypothesis was supported by the attitudes of the Final Year students but not by the First Year medical students. While we would still advocate that First Year medical students should acquire some understanding of and have some formal or informal instruction in, classical Greek and Latin as they pertain to medical terminologies, we acknowledge that Final Year students are likely to have become reasonably well‐versed in the origins of medical terminologies without formal instruction. Clin. Anat. 29:696–701, 2016. © 2016 Wiley Periodicals, Inc.